Accelerated grain refinement during accumulative roll bonding by nanoparticle reinforcement - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Scripta Materialia, 2011)
Ceramic nanoparticles produced by comminution are introduced homogeneously during accumulative roll bonding (ARB) in aluminium AA1050A by airgun spraying from a stabilized aqueous suspension. In the so-produced nanoparticle-reinforced ultrafine-grained material, acceleration of microstructural evolution during the early ARB cycles as well as reduced grain sizes at higher cycles are observed, both caused by additional local straining around the embedded nanoparticles and accompanied by further strengthening. The presented method of nanoparticle application allows homogeneous as well as graded particle distributio